Legal Position of the Professional Disciplinary Council: Central Authority for Disciplinary Enforcement of Medical and Healthcare Professionals in Hospitals - Nurlaelah, Siti; Asgar, Mochamad Ali; Arisman, Arisman; Sari, Diah Ratu (CV. Social Politic Genius (SIGn), 2025)
The transformation of national healthcare governance following the enactment of Law Number 17 of 2023 marks a radical shift in disciplinary enforcement from a regime of professional autonomy to a state-centred one. This centralization of power triggers administrative legal problems regarding the MDP’s institutional independence, which is anomalous in its accountability to the Minister of Health, and gives rise to clashes between procedural authority and the managerial autonomy of healthcare facilities. This research aims to analyze the legal position, procedural supremacy, and material jurisdictional limitations of the MDP as the central authority for the disciplinary enforcement of medical and healthcare professionals. Employing a normative legal research method, this research examines the coherence of norms in the latest regulations. The research results demonstrate that the MDP possesses absolute attributive authority that legally annuls the tradition of collegial dispute resolution, including the prohibition on internal hospital mediation. Functionally, the Council acts as a prejudicial dispute determiner, obliged to issue a recommendation before criminal law enforcement is executed, with jurisdiction confined to 17 types of disciplinary violations. This research concludes that executive dominance in disciplinary enforcement provides legal certainty through the objectivity of violation parameters, yet demands a total restructuring of internal hospital regulations to submit to the supremacy of state administrative law.